Las reformas al Consejo de la Magistratura : oportunidades perdidas para un poder judicial democrático y popular - Méndez Montenegro, Patricio Daniel (2013)
The essay makes an analysis of the different reforms to the Magistracy\nCouncil, especially its composition, attributions and methods used for the selection of\njudges. The essay focuses in the last reform and in the sentence of the Supreme Court\nwhich invalidated this last reform by considering it unconstitutional. In addition to the\nstudy of laws and jurisprudence, the essay analyses the reform from the perspective of\nthe theory of procedure and it ends up considering that we have lost many opportunities\nfor creating an organ of selection, removal of judges and administration of the\nbudget of the Judiciary that could be able to promote an ideological diversity in that\npower, encourage participation and popular control in that organ and making transparent\nthe selection of judges. Finally, the essay includes some possible reforms in that\nsense, that truly represent the guiding principles of this institution.